Tin-gallium co-doped copper oxide-based catalyst as well as preparation method and application thereof
Through the preparation of the tin -meal mixed with copper oxide -based catalysts, the problem of low CO selectivity in the carbon dioxide electrochemical chemistry reaction is solved, and more efficient CO generation and more stable catalytic performance are achieved.
Patent Information
- Application Number
- CN202411578302.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-07
AI Technical Summary
In carbon dioxide electrochemical reduction reactions, CO selectivity is low, and the high cost and scarcity of existing catalysts limit its industrial feasibility.
The tin tin mirror is doped with copper oxide -based catalysts. The preparation methods include scattered copper salt, tin salt, and molten salt in water. After adding a drops of alkaline solution, it is then static, and then hydrophilic reactions, centrifugal separation and dryness.
This catalyst has more stable reaction activity sites, faster electronic transfer rates, more stable performance, and achieve higher electrical catalytic carbon dioxide conversion efficiency, especially in terms of CO's selectivity and activity.
Smart Images

Figure CN119372706A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic reduction of carbon dioxide, and in particular to a tin-gallium co-doped copper oxide-based catalyst and a preparation method and application thereof. Background Art
[0002] Growing energy demand and reliance on fossil fuels have led to increasing CO2 emissions, posing a serious threat to the global environment and climate. To break this cycle and achieve a circular economy, carbon dioxide electrochemical reduction (CO2RR) offers a promising solution to convert CO2 into valuable chemicals and fuels using renewable electricity.
[0003] Among the diverse products of CO2RR, carbon monoxide (CO) is a particularly attractive product because it offers very high economic returns per mole of electrons consumed and can serve as a versatile building block for a variety of organic compounds and liquid fuels as a feedstock. However, pursuing high CO selectivity and activity in CO2RR is challenging due to the complex reaction pathways and fierce competition with the hydrogen evolution reaction (HER). Noble metal catalysts, such as gold (Au) and silver (Ag), exhibit outstanding CO production performance with low onset potentials and high CO selectivity. However, their high cost and scarcity limit their industrial feasibility. To achieve economical and scalable CO2-to-CO conversion, we need to strive to find cost-effective catalysts that can cleverly coordinate key parameters such as low overpotential, high current density, high selectivity, and long durability.
[0004] Copper (Cu) is a unique metal in the field of electrocatalysis. It can significantly activate CO2 and generate a variety of products, including hydrocarbons and oxygenates. However, with its strong activity, Cu also has obvious disadvantages. The selectivity of elemental Cu is poor, especially for single-carbon products such as CO and formate. To address this problem, Cu-based single-atom site catalysts (SACs) have been developed in recent years to improve the selectivity of single-carbon products in CO2RR. By alloying with single-atom metals, the electronic structure of the Cu metal matrix can be fine-tuned to achieve an optimal balance between the desorption and adsorption rates of reactants and intermediates, thereby achieving the desired selectivity for specific products. For example, previous studies have shown that reducing the d-band state of Cu active sites near isolated dopants weakens the CO2RR. * The binding strength of CO2 is enhanced and the adsorption / activation of CO2 is enhanced. This greatly reduces the * -CO * The probability of coupling and inhibiting C 2+ In addition, the Cu catalyst has been shown to be highly mobile in the CO2RR environment and to form active nanoparticles via in situ structural evolution.
[0005] However, the disadvantages of single-atom catalysts are obvious. Since only one element is doped, the active site is single, and the single-atom site is dispersed due to the substrate loading rate problem, the unit density is small, and the overall catalytic performance is limited. Therefore, it is of great significance to study a tin-gallium co-doped copper oxide-based catalyst and its preparation method to improve the selectivity and activity of CO and achieve long-term stability. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a tin-gallium co-doped copper oxide-based catalyst to solve the problem of low CO selectivity in the electrochemical reduction reaction of carbon dioxide in the prior art.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a tin-gallium co-doped copper oxide-based catalyst, comprising the following steps:
[0009] (1) dispersing a copper salt, a tin salt and a gallium salt in water, adding an alkaline solution dropwise and allowing the mixture to stand to obtain a mixture;
[0010] (2) The mixture is subjected to a hydrothermal reaction, centrifugal separation, and drying in sequence to obtain a tin-gallium co-doped copper oxide-based catalyst.
[0011] Preferably, in step (1), the copper salt comprises copper nitrate, copper sulfate or copper chloride; the tin salt comprises tin chloride or tin nitrate; the gallium salt comprises gallium nitrate or gallium chloride; and the alkaline solution is potassium hydroxide solution or sodium hydroxide solution.
[0012] Preferably, in step (1), the molar ratio of copper salt, tin salt and gallium salt is 1:0.01-0.1:0.005-0.05.
[0013] Preferably, in step (1), the molar volume ratio of the copper salt to the alkaline solution is 5-10 mmol:5-15 mL, and the concentration of the alkaline solution is 1-1.5 mol / L.
[0014] Preferably, in step (1), the standing time is 4 to 8 hours.
[0015] Preferably, in step (2), the temperature of the hydrothermal reaction is 120-140° C., and the time of the hydrothermal reaction is 10-14 hours.
[0016] Preferably, in step (3), the drying temperature is 50 to 70° C. and the drying time is 20 to 28 hours.
[0017] The present invention provides a tin-gallium co-doped copper-oxide-based catalyst prepared by the preparation method of the tin-gallium co-doped copper-oxide-based catalyst described above, wherein the tin-gallium co-doped copper-oxide-based catalyst is represented by CuO / Sn x -Ga y , where 0.01≤x≤0.1, 0.005≤y≤0.05.
[0018] The present invention provides an application of the above-mentioned tin-gallium co-doped copper oxide-based catalyst in the electrochemical reduction of carbon dioxide.
[0019] Beneficial effects of the present invention:
[0020] (1) The present invention mainly adopts a water bath method to prepare the catalyst, which has a simple and convenient preparation process, good repeatability, strong controllability, mild processing conditions, short reaction time, low energy consumption, and environmental friendliness. It is suitable for mass production and has certain application prospects.
[0021] (2) The tin-gallium co-doped copper oxide-based catalyst prepared by the present invention has more stable reaction active sites, faster electron transfer rate, more stable performance, and higher electrocatalytic carbon dioxide conversion efficiency compared to other copper-based oxide catalysts of the same type.
[0022] (3) The tin-gallium co-doped copper oxide-based catalyst prepared by the present invention combines the metal base with two single-atom metal additives, tin (Sn) and gallium (Ga). These single atoms work synergistically to change the electronic structure of Cu, which is conducive to the generation of CO and inhibits the hydrogen evolution reaction (HER). At the same time, it also improves the stability of the catalyst by preventing atomic aggregation. The three-metal alloy prepared in the experiment has a Faraday efficiency of more than 99% at a potential of -0.6V (vs RHE), and the current density at this potential is 110mA / cm 2 Around -150mA / cm 2 The long-term stability of up to 75h is maintained, and the FECO is higher than 95%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The CuO / Sn prepared in Example 2 0.02 -Ga 0.005 XRD pattern of the catalyst;
[0024] Figure 2 The CuO / Sn prepared in Example 2 0.02 -Ga 0.005 SEM-EDS images of the catalyst;
[0025] Figure 3 The CuO / Sn prepared in Example 2 0.02 -Ga0.005 Comparison of electrocatalytic performance of the catalyst and the CuO catalyst prepared in Comparative Example 1;
[0026] Figure 4 The CuO / Sn prepared in Example 2 0.02 -Ga 0.005 EIS graphs of the catalyst and the CuO catalyst prepared in Comparative Example 1;
[0027] Figure 5 The CuO / Sn prepared in Example 2 0.02 -Ga 0.005 Cdl diagram of the catalyst and the CuO catalyst prepared in Comparative Example 1. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing a tin-gallium co-doped copper oxide-based catalyst, comprising the following steps:
[0029] (1) dispersing a copper salt, a tin salt and a gallium salt in water, adding an alkaline solution dropwise and allowing the mixture to stand to obtain a mixture;
[0030] (2) The mixture is subjected to a hydrothermal reaction, centrifugal separation, and drying in sequence to obtain a tin-gallium co-doped copper oxide-based catalyst.
[0031] In the present invention, in step (1), the copper salt comprises copper nitrate, copper sulfate or copper chloride; the tin salt comprises tin chloride or tin nitrate; the gallium salt comprises gallium nitrate or gallium chloride; and the alkaline solution is potassium hydroxide solution or sodium hydroxide solution.
[0032] In the present invention, in step (1), the molar ratio of copper salt, tin salt and gallium salt is 1:0.01-0.1:0.005-0.05, preferably 1:0.02-0.08:0.005-0.04, and more preferably 1:0.02:0.005-0.02.
[0033] In the present invention, in the step (1), the molar volume ratio of the copper salt to the alkaline solution is 5-10 mmol:5-15 mL, preferably 5 mmol:10 mL, 10 mmol:10 mL, and the concentration of the alkaline solution is 1-1.5 mol / L, preferably 1.1-1.4 mol / L, and more preferably 1.2-1.3 mol / L.
[0034] In the present invention, the alkaline solution is added dropwise within 1 minute; the copper salt, tin salt and gallium salt are dispersed in water, and after the alkaline solution is added dropwise, the mixture is preferably stirred for 1 hour and then allowed to stand.
[0035] In the present invention, in step (1), the standing time is 4 to 8 hours, preferably 5 to 7 hours, and more preferably 6 hours.
[0036] In the present invention, in step (2), the temperature of the hydrothermal reaction is 120-140°C, preferably 125-135°C, and more preferably 130°C; the time of the hydrothermal reaction is 10-14h, preferably 11-13h, and more preferably 12h.
[0037] In the present invention, in the step (3), the drying temperature is 50-70°C, preferably 55-65°C, and more preferably 60°C; the drying time is 20-28h, preferably 22-26h, and more preferably 24h.
[0038] The present invention provides a tin-gallium co-doped copper-oxide-based catalyst prepared by the preparation method of the tin-gallium co-doped copper-oxide-based catalyst described above, wherein the tin-gallium co-doped copper-oxide-based catalyst is represented by CuO / Sn x -Ga y , where 0.01≤x≤0.1, 0.005≤y≤0.05.
[0039] In the present invention, x represents the molar ratio of tin to copper oxide, and y represents the molar ratio of gallium to copper oxide.
[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0041] Example 1
[0042] 5mmolCu(NO3)2·3H2O, 0.1mmolSnCl4·5H2O and 0.05mmolgallium nitrate were dissolved in 50mLdeionized water and stirred evenly. Then, 10mLpotassium hydroxide solution (concentration of 1.2mol / L) was added dropwise within 1 minute. After stirring for 1h, the mixture was allowed to stand at room temperature for 6h. The mixture was transferred to a 100mL polytetrafluoroethylene liner and then placed in a hydrothermal reactor. The temperature was raised to 130°C and kept at 130°C for 12h. After the reaction was completed, the reaction product was cooled to room temperature, centrifuged and separated by centrifugation, washed three times with anhydrous ethanol, and finally dried in a vacuum drying oven at 60°C for 24h to obtain CuO / Sn 0.02 -Ga 0.01 catalyst.
[0043] Example 2
[0044] The difference from Example 1 is that the amount of Cu(NO3)2·3H2O is 10 mmol, the amount of SnCl4·5H2O is 0.2 mmol, and the CuO / Sn 0.02 -Ga 0.005 catalyst, and other conditions were the same.
[0045] Example 3
[0046] The difference from Example 1 is that the amount of gallium nitrate used is 0.1 mmol, and the CuO / Sn 0.02 -Ga 0.02 catalyst, and other conditions were the same.
[0047] Comparative Example 1
[0048] Dissolve 5mmolCu(NO3)2·3H2O in 50mL of deionized water and stir evenly. Then, add 10mL of potassium hydroxide solution (concentration of 1.2mol / L) dropwise within 1 minute. Continue stirring for 1h and let stand at room temperature for 6h. Then, transfer to a 100mL polytetrafluoroethylene liner and place in a hydrothermal reactor. Raise its temperature to 130°C and keep it at 130°C for 12h. After the reaction is completed, the reaction product is cooled to room temperature, centrifuged in a centrifuge, washed three times with anhydrous ethanol, and finally placed in a vacuum drying oven at 60°C for 24h to obtain a CuO catalyst.
[0049] Figure 1 The CuO / Sn prepared in Example 2 0.02 -Ga 0.005 The XRD pattern of the catalyst Figure 1 It can be seen that CuO / Sn 0.02 -Ga 0.005 The peak position of CuO / Sn is consistent with that of copper oxide, which proves that 0.02 -Ga 0.005 The catalyst is mainly a copper oxide structure, and doping does not change the structure of copper oxide.
[0050] Figure 2 The CuO / Sn prepared in Example 2 0.02 -Ga 0.005 SEM-EDS image of the catalyst. From the SEM image, we can see that CuO / Sn 0.02 -Ga 0.005 The catalyst is a flake structure, and the EDS image proves that CuO / Sn 0.02 -Ga 0.005 There are two elements Sn and Ga in the catalyst, and the two doping elements are evenly distributed in the catalyst.
[0051] Figure 3 The CuO / Sn prepared in Example 2 0.02 -Ga 0.005 The electrocatalytic performance comparison of the CuO catalyst prepared in Example 1 is shown in FIG. Figure 3It can be seen that within the tested potential range, whether in terms of Faraday efficiency or current density, the performance of copper oxide doped with Sn and Ga is significantly improved.
[0052] Figure 4 The CuO / Sn prepared in Example 2 0.02 -Ga 0.005 The EIS graphs of the CuO catalyst prepared in the catalyst and Comparative Example 1 show that Figure 4 It can be seen that the doping of tin and gallium diatoms reduces the impedance of the catalyst and increases the speed of charge transfer, which indicates that diatomic doping improves the efficiency of the catalyst.
[0053] Figure 5 The CuO / Sn prepared in Example 2 0.02 -Ga 0.005 The Cdl diagram of the CuO catalyst prepared in the catalyst and Comparative Example 1 is shown in FIG. Figure 5 It can be seen that the doping of tin and gallium diatoms increases the Cdl value of the catalyst, proving that more accessible active sites are exposed on its surface. The more active sites in the same area, the more conducive to catalysis.
[0054] Specific test plan:
[0055] (1) Preparation of the catalyst negative electrode: The CuO / Sn prepared in Example 2 0.02 -Ga 0.01 The catalyst or comparative example 1 was prepared by mixing 10 mg of the catalyst with 0.5 ml of ethanol (concentration of 97%), 0.5 ml of deionized water, and 0.05 ml of Nafion perfluorinated resin binder (concentration of 5 wt%, DuPont520), and ultrasonicating for 15 min to obtain a mixed solution, which was then dropped onto the black surface of 1*1 cm gas diffusion carbon paper (SGL-29bc) and dried naturally.
[0056] (2) Assemble the prepared catalyst negative electrode, platinum counter electrode, and mercury / mercury oxide reference electrode into a flow cell electrolytic cell.
[0057] (3) The test requires the use of a CH electrochemical workstation, a gas chromatograph, a peristaltic pump, 80 ml of potassium hydroxide solution (concentration 1 M) as the electrolyte, a peristaltic pump speed of 10 rpm, and CO2.
[0058] (4) The catalyst electrode was electro-reduced in a potassium hydroxide solution electrolyte without CO2 at a voltage of -0.6V (vs. RHE) for 30 minutes, and then normal testing was performed with CO2: the appropriate potential was set, and each potential test was performed for 1 hour. The test results are as follows: Figure 3 shown.
[0059] It can be seen from the above embodiments that the present invention provides a tin-gallium co-doped copper oxide-based catalyst and its preparation method and application, firstly, copper salt, tin salt and gallium salt are dispersed in water, and an alkaline solution is added dropwise and then allowed to stand to obtain a mixture; then the mixture is subjected to a hydrothermal reaction, centrifugal separation and drying in sequence to obtain a tin-gallium co-doped copper oxide-based catalyst. Compared with other copper-based oxide catalysts of the same type, the tin-gallium co-doped copper oxide-based catalyst prepared by the present invention has more stable reaction active sites, faster electron transfer rate, more stable performance, and higher electrocatalytic carbon dioxide conversion efficiency.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a tin-gallium co-doped copper oxide-based catalyst, characterized in that: The steps include: (1) dispersing a copper salt, a tin salt and a gallium salt in water, adding an alkaline solution dropwise and allowing the mixture to stand to obtain a mixture; (2) The mixture is subjected to a hydrothermal reaction, centrifugal separation, and drying in sequence to obtain a tin-gallium co-doped copper oxide-based catalyst.
2. The method for preparing a tin-gallium co-doped copper oxide-based catalyst according to claim 1, characterized in that: In the step (1), the copper salt comprises copper nitrate, copper sulfate or copper chloride; the tin salt comprises tin chloride or tin nitrate; the gallium salt comprises gallium nitrate or gallium chloride; and the alkaline solution is potassium hydroxide solution or sodium hydroxide solution.
3. The method for preparing a tin-gallium co-doped copper oxide-based catalyst according to claim 2, characterized in that: In the step (1), the molar ratio of the copper salt, the tin salt and the gallium salt is 1:0.01-0.1:0.005-0.
05.
4. The method for preparing a tin-gallium co-doped copper oxide-based catalyst according to any one of claims 1 to 3, characterized in that: In the step (1), the molar volume ratio of the copper salt to the alkaline solution is 5-10 mmol:5-15 mL, and the concentration of the alkaline solution is 1-1.5 mol / L.
5. The method for preparing a tin-gallium co-doped copper oxide-based catalyst according to claim 4, characterized in that: In the step (1), the standing time is 4 to 8 hours.
6. The method for preparing a tin-gallium co-doped copper oxide-based catalyst according to claim 2, 3 or 5, characterized in that: In the step (2), the temperature of the hydrothermal reaction is 120 to 140° C., and the time of the hydrothermal reaction is 10 to 14 hours.
7. The method for preparing a tin-gallium co-doped copper oxide-based catalyst according to claim 6, characterized in that: In the step (3), the drying temperature is 50 to 70° C. and the drying time is 20 to 28 hours.
8. The tin-gallium co-doped copper oxide-based catalyst prepared by the method for preparing the tin-gallium co-doped copper oxide-based catalyst according to any one of claims 1 to 7, characterized in that: The Sn-Gallium co-doped CuO-based catalyst is denoted as CuO / Sn x -Ga y , where 0.01≤x≤0.1, 0.005≤y≤0.
05.
9. Use of the tin-gallium co-doped copper oxide-based catalyst according to claim 8 in the electrochemical reduction of carbon dioxide.
Citation Information
Patent Citations
Metal monatomic ligand loaded copper oxide nanosheet catalyst as well as preparation method and application thereof
CN116065181A
Gallium-tin alloy catalyst for preparing isopropanol by electrically reducing carbon dioxide as well as preparation method and application of gallium-tin alloy catalyst
CN117431565A